Enhancing Electron Transport in Silicon Self-Switching Devices: A Study on Triangular Barrier-Induced Ballistic Effects - Yi Liang Tan; Nor Farhani Zakaria; Shahrir Rizal Kasjoo; Mohd Fairus Ahmad; Zarimawaty Zailan; Mohd Natashah Norizan; Ili Salwani Mohama; Banu A Poobalan; Faradilla Aziz; Arun Kumar Singh, (International Journal of Nanoelectronics and Materials (IJNeaM), 2026)
With the increasing demand for high-frequency applications due to congestion in lower frequency bands, the need for high-performance diode detectors has become critical. Achieving fast, efficient, high-frequency response requires diodes with strong rectifying capability and sharp nonlinearity. These electrical characteristics, particularly the I–V behavior of the device, strongly influence key performance metrics such as the curvature coefficient and current responsivity. Derived from the I–V curve shape, these metrics reflect the device’s nonlinear behavior. This study investigates how geometrical modifications influence ballistic transport and electrical performance in silicon-based self-switching devices (SSDs). A triangular potential barrier is introduced within the channel to promote ballistic-like electron transport, especially when the channel dimensions are comparable to or smaller than the mean free path (MFP) of charge carriers. Device structures are designed using Silvaco Devedit 3D and simulated in ATLAS. I–V characteristics, hole velocity, and electric field are extracted from Tonyplot. Among the simulated structures, both the fully triangular and the integrated trench designs exhibit substantially higher hole velocities and localised electric fields. Furthermore, the SSD with integrated planar and triangular trenches exhibited asignificantly increased forward current, indicating stronger ballistic-like behaviour. This geometry is considered the most promising within the scope of the simulations, with its narrow trench width and short channel length suggesting the possibility of quasi-ballistic or ballistic-like transport. Results further indicate that both the size and shape of the triangular barrier critically affect electrical characteristics, showing their importance for future SSD optimization.